2022
DOI: 10.1097/j.jcrs.0000000000000996
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of axial length measurements in silicone oil–filled eyes using SS-OCT and partial coherence interferometry

Abstract: The OA2000 is the preferred biometer for axial length measurement in silicone oil–filled eyes. The IOLMaster 500 and IOLMaster 700 overestimate the axial length, and the measurement errors increase with longer axial length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The larger hyperopic error and the correlation between PE and AL in the silicone oil subgroup suggested that there may be systematic errors in the AL measurement of silicone oil-filled eyes with IOL-Master 700, thereby confirming our earlier findings. 28 Scleral buckling surgery alters the ocular structure, resulting in a longer AL and shallower ACD compared with preoperative measurements. [29][30][31] These changes in turn affect the IOL calculation, but the prediction accuracy for such patients remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The larger hyperopic error and the correlation between PE and AL in the silicone oil subgroup suggested that there may be systematic errors in the AL measurement of silicone oil-filled eyes with IOL-Master 700, thereby confirming our earlier findings. 28 Scleral buckling surgery alters the ocular structure, resulting in a longer AL and shallower ACD compared with preoperative measurements. [29][30][31] These changes in turn affect the IOL calculation, but the prediction accuracy for such patients remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The larger hyperopic error and the correlation between PE and AL in the silicone oil subgroup suggested that there may be systematic errors in the AL measurement of silicone oil-filled eyes with IOLMaster 700, thereby confirming our earlier findings. 28…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the AL data we used were obtained from the IOL Master with the status of SO-filled eyes. To address potential overestimation by the IOL Master for the AL in long eyes ( 22 ), our study applied the Wang-Koch adjustment to the AL of patients with an AL of >26 mm. Regarding anterior chamber depth (ACD), it has been reported that the increase in ACD in SO-injected patients after pars plana vitrectomy returns to preoperative values within 1 month of surgery ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Four traditional formulas were also assessed, including Haigis et al (2000) Hoffer (1993, 2007, Holladay et al (1988) and SRK/T (Retzlaff et al, 1990). The formulas were calculated to determine the predicted postoperative spherical equivalent refraction of the implanted IOL power using measured AL and corrected AL with silicone oil adjustment (SO AL = 0.9478 × measured AL +1.1984), (Zhang et al, 2022) respectively. The User Group for Laser Interference Biometry (ULIB) constants were used (available at www.…”
Section: Formula Calculationmentioning
confidence: 99%